Parenting and Grandparenting: Perceived about Emotional Autonomy of Teenagers - Dewi Seftia Rosyidatul Hilaliyyah; Dinie Ratri Desiningrum (International Journal Labs, 2022)
Childcare by grandparents has been getting more and more attractive to be studied.The purpose of this study was to look at the perception of parents and grandparents to the emotional autonomy of teenagers whose fosterage. Qualitative studies using the method Interpretative Phenomenological Analysis (IPA) conducted on 4 parents in middle aged and 4 early elderly, who nurture for adolescents aged 12-15 years, subject has come from Central Java Indonesia. Researchers found that elderly perceived that they more than middle adulthood in assess about lack of responsibility of teens for daily personal tasks, to solve everyday problems and makes decisions, lack of ability to express their opinions and lack to creatively generate new ideas. The whole subject feels that grandparents tends to be permissive, because the elderly want their grandchildren has quiet and do not whine or get angry against the grandparents, but their agree that firmness against children in the parenting methods are needed to discipline the child.